Psychosis as first manifestation of autoimmune encephalitis against N-methyl-D-aspartate receptors (ECR-NMDA). Case Report - Paz Caldas, María Alejandra (2023)
The case of a 21-year-old man, hospitalized in the psychiatric service of a general hospital with a history of abnormal thought, perception, and behavioral processes, reaching a suicidal attempt, is presented. In the psychiatric hospitalization unit, he experienced a torpid clinical course, including the appearance of involuntary movements and a progressive sensory disorder that led to his transfer to the Intermediate Care Unit of the Internal Medicine Service. After laboratory tests, imaging support and evaluation by different medical specialties, the final diagnosis was a clinical picture compatible with NMDA anti-receptor encephalitis.